PELATIHAN PEMBUATAN KEMASAN YANG KEKINIAN UNTUK PRODUK BATIK TIGA NEGERI KHAS SURAKARTA - Apika Nurani Sulistyati; Theresia Widiastuti (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Batik Tiga Negeri is one of the historic batiks on the north coast of the island of Java which was made to be traded from the start. Packaging for Batik Tiga Negeri is needed in addition to protecting the product, as well as for communication media in spreading about one of the nation's wealth that can be proud of. Packaging can have a useful multi-function. There are many packaging options, ranging from plastik to paper and cloth, all of which can display product labels. Through this service activity, it is hoped that the millennial generation, namely Regina Pacis Solo High School students will understand: 1) How far can the main motifs of Batik Tiga Negeri developed according to the style of young people? 2) How student’s creativity in making packaging for Batik Tiga Negeri products is not only attractive, useful, but also can be an effective communication medium. In other words, from the work produced, it will further clarify the role of packaging for Batik Tiga Negeri handicraft products other than as a wrapper. The method used is community service in the form of training. Beginning with providing material to young people as the nation's next generation, about the archipelago's wastra, especially batik. Training on making designs on packaging to wrap Tiga Negeri batik products, in order to produce a unique packaging with the main motif idea of Batik Tiga Negeri. The purpose of this activity is to make students aware of the importance of maintaining the ancestral heritage which is the wealth of this nation.